2008
DOI: 10.1016/j.pain.2007.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesic THerapy Observational Survey (PATHOS): A practice pattern study in 7 Central/Southern European countries

Abstract: Surveys evaluating pain in hospitals keep on showing that postoperative pain (POP) remains undertreated. At the time when guidelines are edited and organisational changes are implemented, more recent data are necessary to check the impact of these measures on daily practice and needs for improvement. This prospective, cross-sectional, observational, multi-centre practice survey was performed in 2004-2005 in 7 European countries. It was conducted in surgical wards of a randomised sample of hospitals. Data on PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
0
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 32 publications
5
115
0
21
Order By: Relevance
“…Our survey reveals a high frequency of pain reporting (> 90%) in surgical wards, comparing favorably with previous French surveys ❞ in 1996 (0% reporting) [48] and 2000 (64-82% reporting) [30], recent surveys in Germany (53.4% reporting) [61], the United Kingdom (57% reporting) [59] and a recent European declarative survey (44% reporting) [8]. It has been suggested that educating nurses about pain and daily pain assessment with a numerical rating scale can improve the communication, assessment and documentation of patients' pain [23] and improve analgesic administration by nurses [24].…”
Section: Discussion (1382 Words)supporting
confidence: 81%
See 4 more Smart Citations
“…Our survey reveals a high frequency of pain reporting (> 90%) in surgical wards, comparing favorably with previous French surveys ❞ in 1996 (0% reporting) [48] and 2000 (64-82% reporting) [30], recent surveys in Germany (53.4% reporting) [61], the United Kingdom (57% reporting) [59] and a recent European declarative survey (44% reporting) [8]. It has been suggested that educating nurses about pain and daily pain assessment with a numerical rating scale can improve the communication, assessment and documentation of patients' pain [23] and improve analgesic administration by nurses [24].…”
Section: Discussion (1382 Words)supporting
confidence: 81%
“…We found that non opioid analgesics were more widely prescribed in France (95.5%) than in a European survey in which intravenous non opioid drugs formed part of the first-line analgesic treatment after major surgery according to 64 to 72% of respondents (depending upon surgery type), and balanced analgesia use in more than 75% of patients was declared by 71% of respondents [8]. A combination of two non opioid analgesics with morphine may be considered optimal balanced analgesia [22].…”
Section: Discussion (1382 Words)mentioning
confidence: 82%
See 3 more Smart Citations